Analysis of PM2.5 spatial association evolution in the Sichuan Basin and its driving factors - Li, Zeqiong; Wu, Boqing; Wu, Wenjuan (Frontiers in Environmental Science, 2023)
We investigated the evolution of spatiotemporal patterns of particulate matter with diameter not greater than 2.5m (PM2.5) across eighteen cities in the Sichuan Basin. In addition, a spatial association network was characterized through social network analysis, using China’s air monitoring data and relevant socioeconomic data. The results were as follows: (1) A significant reduction in PM2.5 emissions in the Sichuan Basin occurred from 2015 to 2020, but challenges remain: the number of cities with a PM2.5 annual concentration above 35.00 µg/m3 decreased from seventeen to six, and the annual concentration declined from 62.92 µg/m3 to 40.83 µg/m3 in Chengdu and from 55.08 µg/m3 to 32.67 µg/m3 in Chongqing. PM2.5 concentrations were the highest in the winter, around 1.50‒2.00 times the annual concentration. (2) The PM2.5 overall network displayed significant spatial association with periodic changes, implying that the inter-city association strengthened, then weakened, and then strengthened again from 2015 to 2019 despite a sharp drop in the PM2.5 concentration. Network density remained at 0.29 between 2015 and 2019 but increased to 0.30 in 2017, efficiency increased from 0.72 to 0.80 and connectedness from 0.78 to 1.00. A “core-edge” pattern explicitly presented that Chengdu and Chongqing were located at the center with degree of 94.40 and 82.35, respectively, while other cities marginalized less than 35.30. (3) The driving factors of network structure were explored by quadratic assignment procedure, which showed that enlarging the difference in gross domestic product gap between secondary and tertiary industries and urban population and narrowing the difference among urban ratio, the number of civilian vehicle, and distance between cities efficiently promotes the PM2.5 spatial association in Sichuan Basin.